Formulasi Cookies Berbahan Dasar Tepung Tempe dan Tepung Bayam Merah untuk PMT Balita - Maria Dolorosa Peni Sogen; Oktavina Permatasari; Ariani Damayanti; Maria Magdalena Meilina Rahmawati (Jurnal Kesehatan, 2022)
Health problems, especially diet, are a problem in almost all countries. In Indonesia, the prevalence of nutrition is a serious problem and has not been fully addressed. Data from the Basic Health Survey (Riskesdas) in 2018 revealed that the prevalence of undernourished children under five was 11.4% and the prevalence of malnourished children was 3.8%. One of the efforts to increase the weight of toddlers is through the provision of supplementary food (PMT) which contains high protein and high calories. One type of PMT that meets these needs is by providing fortified cookies. Cookies with fortified tempeh flour and red spinach flour can be an alternative in giving PMT. This study aims to determine the right formulation in the manufacture of PMT Toddler cookies with the basic ingredients of tempeh flour and red spinach flour. This type of qualitative research with experimental methods. The study used a completely randomizesd design (CRD). The cookie formulation is divided into four formulations, namely F1 (control formulation), F2, F3, and F4. The treatment carried out in this study was the difference in the composition of the raw materials used and tested for the characteristics of cookies. The four formulations were tested for preference by semi-trained panelists, namely mothers who had toddlers as many as 30 panelists. The conclusion in this study was that the panelists preferred F3 cookies based on the parameters of taste, color, and texture. Cookies F3 are cookies with a substitution of 50% tempeh flour and 10% red spinach flour